FAKTOR PENYEBAB PERILAKU MEMBOLOS PESERTA DIDIK DAN UPAYA GURU BK DALAM MENGATASINYA - Sari, Ria Permata (Bimbingan dan Konseling, 2014)
The phenomena at school, there are still some students do the truancy and played outside the school area during learning process. The research is to describe: 1) The internal factor that cause the students truancy, 2) The external factor that cause the students truancy and 3) The effort of counselor to overcome such problems. The research is qualitative descriptive with informant 5 students, 4 counselors and 5 parents. The data was collected through the interview and the validity of the data was tested by using triangulation of data, the collected data were analyzed with the interactive model consists of data collection, data reduction, display data and summary. The results of this study revealed the factors that cause truancy such as: 1) The internal factors no motivation and interest from the students itself and the physiology interference that disturb the students in studying, 2) The external factors no control from their parents, while the factor from the school was the teachers method in teaching that was not interesting to them, the way the teacher taught was hardly to be understood, so the students got bored to study, from the society what made the students truancy was certain behavior of society that bother their studying, 3) The effort counselor to overcome the students truancy observing the students behavior, do the cooperation with the school, giving the counseling and the summon letter to the parents.